UiTM student guidebook mobile application / Mohammad Hafidz Rahmat … [et al.] - Rahmat, Mohammad Hafidz; Kushan, Albin Lemuel; Ahmad, Zaaba; Abdul Rahid, Nurul Najwa; Mohd Nasib, Nabihah (Division of Research and Industry Linkages, 2017)
UiTM is the largest university in Malaysia which comprises one main campus, thirteen automous campuses and twenty one satellite campuses. Currently, UiTM houses approximately 168000 students and 17000 staffs. Due to high number of student admission each semester, delivering information to new student can be inefficient and miscommunication could occur. Nowadays, information can be easily accessed and obtained through the means of mobile technology. Hence, the UiTM Student Guidebook is proposed and developed to address the issues arise. The UiTM Student Guidebook provide a platform for students to conveniently accessed relevant information regarding UiTM in general and assist them by providing information on student’s frequently asked question. For now, UiTM Jasin campus is chosen to be the pioneer campus for this project and all the information is gathered from the Student Affairs Division of UiTM Jasin Campus. This application is developed for Android-based smartphones and most of the information can be accessed offline. This project aim is to provide assistant to UiTM students especially newly registered students and hopefully can be expanded to cater other campuses.